Co-creation of a scalable, climate service tool for the sustainable management of key blue economy sectors in the Spanish Mediterranean coast - de la Vara, Alba; Cabos, William; Ferri, Mireia; Ferrando, Maite (Frontiers in Climate, 2025)
The Mediterranean region is experiencing rapid warming, outpacing the global average, and is frequently impacted by extreme weather events like heatwaves and heavy precipitation. Climate models project an increase in the frequency and/or intensity of these events, which pose a significant risk of negative socio-economic impacts—particularly in the Western Mediterranean regions, such as the Spanish Mediterranean coast. Negative socio-economic impacts affect to a greater extent climate-exposed sectors such as the blue economy, which is defined as the economic activities associated with seas and oceans. Therefore, the development of climate service tools tailored to the needs and expectations of potential end-users from these sectors is crucial. This manuscript details the hybrid methodology adopted for the creation of the ECOAZUL-MED climate service tool, as well as its interface and main functionalities. The tool offers stakeholders from aquaculture, fisheries and coastal tourism along the Spanish Mediterranean coasts, for the first time, climate information from air-sea coupled simulations from the Med-CORDEX initiative to promote evidence-based decision-making regarding adaptation. Our work highlights the relevance of using bottom-up and participatory approaches combining quantitative and qualitative methodologies to generate tailored climate service tools adapted to the local context. Stakeholders’ feedback, compiled through focus groups, workshops and questionnaires presented in this manuscript, was key to setting the contents of the tool and its final interface. Insights that emerge from this work allow us to highlight the importance of using participatory approaches to reinforce the long-lasting use of climate tools as they are designed based on stakeholders’ inputs, and to propose this methodology to be applied in other contexts to build sustainable climate tools.